ANALYSIS OF LANGUAGE POLITICS AND SPEECH ACTIONS IN THE JANUARY 2023 EPISODE OF MATA NAJWA'S TALK SHOW PROGRAM - Oktafiani, Nurul; Anggraini, Nori; Siafri, Frimadhona (Universitas Muhammadiyah Tangerang, 2023)
Errors in writing absorption elements were not found in the thesis of Indonesian Language and Literature Education students Batch 2022. Errors in the use of effective sentences in the thesis of Indonesian Language and Literature Education students Batch 2022 found 123 cases of errors. These errors are caused by excessive sentences/words and improper choice of words/diction. The cause of the occurrence of these errors because of the lack of thoroughness of students when writing thesis. It can be seen that there is a removal of phoneme elements in a word and sentences that are redundant or redundant so that the sentence becomes ineffective